Subtotal versus total gastrectomy for mid- and distal gastric poorly cohesive carcinoma: a retrospective controlled study - Dinçer, Burak; Sağdıç, Mehmet Furkan; Olgun, Mehmet; Karayiğit, Ahmet; Dilek, Gülay Bilir; Sarıdemir, Serdar; Özaslan, Cihangir (Frontiers in Oncology, 2025)
BackgroundSubtotal gastrectomy is frequently performed for distally located gastric tumors and carries a lower risk of postoperative complications compared to total gastrectomy. However, due to the submucosal spread pattern and worse prognosis of poorly cohesive carcinoma (PCC), some authors advocate for routine total gastrectomy. This study aimed to compare the outcomes of subtotal versus total gastrectomy in patients with mid- and distal-located gastric PCC.MethodsThis single-center retrospective study included patients who underwent resection for gastric PCC between 2012 and 2024. Exclusion criteria were systemic metastasis, palliative surgery, and tumors located in the proximal one-third of the stomach. Patients were analyzed based on demographic, clinical, pathological, and survival data.ResultsA total of 154 patients were included. The median age was 62 years (range: 36–87), and 83 patients (53.9%) were male. Subtotal gastrectomy was performed in 70 patients (45.5%). The median pathological tumor diameter was 60 mm (IQR: 40–90). Over a median follow-up of 79 months, 33 locoregional and 81 systemic recurrences were observed among 146 patients, and 53 patients (36.3%) were alive at the time of last follow-up. Pathological stage was the only independent factor associated with overall survival, while the type of surgery (subtotal vs. total gastrectomy) did not significantly affect survival outcomes.ConclusionOur study demonstrated that subtotal gastrectomy yielded oncologic outcomes similar to those achieved with total gastrectomy in mid- and distal gastric poorly cohesive carcinoma cases.